Efektivitas Penggunaan Buku Pop-Up Pada Pembelajaran Tematik Ditinjau dari Hasil Belajar Kelas III Madrasah Ibtidaiyah Asy-Syafi’iyah - Salsabila, Annisa; Raehang, Raehang; Agus, Imaludin (IAIN Kendari, 2023)
This study aims to find out the effectiveness of using Pop-Up book media in thematic learning of grade III of Madrasah Ibtidaiyah Asy-Syafi'iyah. The type of research used in this study is quantitative research with pre-experiment method. The research design used is One Group Pretest-Posttest Design. The population in this study is all students in grade III of Madrasah Ibtidaiyah Asy-Syafi'iyah consisting of classes III A and III B, the population is too much so the researcher chooses the population by using the sample technique